Effect of hypoxia and nitrate supplementation on different high-intensity interval-training sessions - Sousa, A.; Viana, J. L.; Milheiro, J.; Reis, V. M.; Millet, G. I. (European Journal of Applied Physiology, 2021)
Purpose: To test the hypothesis that interval-training (IHT) would be impaired by hypoxia to a larger extent than repeated-sprint training (RSH) and that dietary nitrate (NO3-) would mitigate the detrimental effect of hypoxia to a larger extent during IHT than RSH. Methods: Thirty endurance-trained male participants performed IHT (6 × 1 min at 90%? with 1 min active recovery) and RSH (2 sets of 6 × 10 s "all-out" efforts with 20 s active recovery) on a cycle ergometer, allocated in one of three groups: normobaric hypoxia (~ 13% FiO2) + NO3- - HNO, n = 10; normobaric hypoxia + placebo - HPL, n = 10; normoxia (20.9% FiO2) + placebo - CON, n = 10. Submaximal oxygen uptake (V.O2), time spent above 90% of maximal V.O2 (= 90 V.O2max) and heart rate (= 90 HRmax) were compared between IHT and RSH sessions and groups. Additionally, mean power output (MPO), decrement score and % of power associated with V.O2max (%pV.O2max) in RSH sessions were analyzed. Results: VO2 at sub-maximal intensities did not differ between training protocols and groups (~ 27 ml kg-1 min-1). = 90 HRmax was significantly higher in IHT compared to RSH session (39 ± 8 vs. 30 ± 8%, p = 0.03) but only in HNO group. MPO (range 360-490 W) and decrement score (10-13%) were similar between groups although %pV.O2max was significantly higher (p = 0.04) in CON (166 ± 16 W) compared with both HPL (147 ± 15 W) and HNO (144 ± 10 W) groups. Conclusion: IHT responses were neither more impaired by hypoxia than RSH ones. Moreover, dietary NO3- supplementation impacted equally IHT and RSH training responses` differences between hypoxia and normoxia.